Advocacy of Women in Tourism Indonesia as an Implementation of Sustainable Development Goals Number 5 - Renaningtyas, Maria Agatha; Nugraha, A.A Bagus Surya Widya (Pusat Studi Gender Universitas Jember, 2025)
This research discusses advocacy efforts by Women in Tourism Indonesia (WTID) as an implementation of Sustainable Development Goals (SDGs) number 5, namely gender equality. As an organization that focuses on tourism and gender equality, WTID advocates in related fields to realize its goal of creating gender-inclusive tourism. This research explains the form of advocacy carried out by WTID to realise gender-equitable sustainable development. This research uses descriptive qualitative methods by collecting primary and secondary data. Primary data is in the form of interviews with WTID resource persons and secondary data is in the form of literature related to the topic discussed. Based on the data that has been obtained, it can be concluded that the advocacy programme by WTID is in line with the principles and indicators of SDGs number 5, namely gender equality. The implementation of advocacy carried out by WTID is in the form of research on sexual violence in the tourism industry, inclusive tourism webinars involving tourism actors and disability groups, and hearings related to gender issues in tourism with the government as a policy maker.